The change : a novel - Miller, Kirsten, 1973- (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"Big Little Lies meets The Witches of Eastwick--a gloriously entertaining and knife-sharp feminist revenge fantasy about three women whose midlife crisis brings unexpected new powers--putting them on a collision course with the evil that lurks in their wealthy beach town"--